Role of lubricating oil properties in exhaust particle emissions of an off-road diesel engine - Ovaska, Teemu; Niemi, Seppo; Sirviö, Katriina; Nilsson, Olav; Karjalainen, Panu; Rönkkö, Topi; Kulmala, Kari; Keskinen, Jorma (SAE International, 2020)
Particle number emissions from an off-road diesel engine without exhaust after-treatment were studied by using five different heavyduty lubricating oils in the engine. The study extends understanding on how the properties of lubricating oil affect the nanoparticle emissions from an off-road diesel engine. The lubricants were selected among the performance classes of the European Automobile Manufacturers Association, at least one lubricant from each category intended for heavy-duty diesel engines. Particle size distributions were measured by the means of an engine exhaust particle sizer (EEPS), but soot emissions, gaseous emissions and the basic engine performance were also determined. During the non-road steady state cycle, the most of the differences were detected at the particle size range of 6–15 nm. In most cases, the lowest particle quantities were emitted when the highest performance category lubricant was used. Based on the results of this study, the low contents of Zn, P, and S in lubricating oil contributed to the reduced emission factors for engineout nucleation mode particles at any load. In addition, the low content of sulfate ash was considered the main influential factor for the low particle number emissions.
Keywords: fi=Sähkötekniikka|en=Electrical Engineering|